2004
DOI: 10.1088/1126-6708/2004/03/063
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian structure and noncommutativity inp-brane models with exotic supersymmetry

Abstract: The Hamiltonian of the simplest super p-brane model preserving 3/4 of the D = 4 N = 1 supersymmetry in the centrally extended symplectic superspace is derived and its symmetries are described. The constraints of the model are covariantly separated into the first-and the second-class sets and the Dirac brackets (D.B.) are constructed. We show the D.B. noncommutativity of the super p-brane coordinates and find the D.B. realization of the OSp(1|8) superalgebra. Established is the coincidence of the D.B. and Poiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Note that supersymmetry and generalized translation generator densities do not contain any ghost contribution. One can check that the P.B.-commutation relations of the OSp(1|8) superalgebra extended by the ghost contributions coincide with the P.B.-commutation relations of the original OSp(1|8) superalgebra [17].…”
Section: Brst Charge and Osp(1|8) Symmetry Generatorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Note that supersymmetry and generalized translation generator densities do not contain any ghost contribution. One can check that the P.B.-commutation relations of the OSp(1|8) superalgebra extended by the ghost contributions coincide with the P.B.-commutation relations of the original OSp(1|8) superalgebra [17].…”
Section: Brst Charge and Osp(1|8) Symmetry Generatorsmentioning
confidence: 94%
“…The Hamiltonian structure of the action (4), described in [17], is characterized by 3 fermionic and 2p + 7 bosonic first-class constraints that generate its local symmetries, as well as, 1 fermionic and 8 bosonic second-class constraints taken into account by the construction of the Dirac bracket. We found that the D.B.…”
Section: Conversion Of Tensionless Super P-brane Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…of (29) vanishes after integration with respect to σ and σ ′ . Thus, the BRST charge Ω (22) between Ω and other OSp(1|8) symmetry charges G ≡ d p σG(τ, σ) extended by the ghost contributions will also be preserved, because of the general relation (17) for the generator densities:…”
Section: Brst Charge and Osp(1|8) Symmetry Generatorsmentioning
confidence: 99%
“…The presence of the second-class constraints necessitates introduction of the Dirac brackets (DB) that in general essentially complicates analysis of the Hamiltonian dynamics (see, e.g. [40]) so it is convenient to treat the constraint y 2 +1 ≈ 0 as a gauge-fixing condition for the first-class constraint (y• p) ≈ 0 that generates dilatations of the embeddingspace coordinates [41]. Gauged dilatations implement the projective-space realization of Ad S d , so the set of the two first-class constraints (y • p) ≈ 0 and p 2 ≈ 0 can be taken as the starting point for description of the massless particle (tensionless string zero modes) models in such an approach.…”
Section: Introductionmentioning
confidence: 99%